НОРЕАЛИСТИК ҲИКОЯДА УСЛУБ РАНГ-БАРАНГЛИГИ - Алланазарова, Ф.К. (SCIENCE and SOCIETY, 2021)
The article analyzes the factors of manifestation of the originality of unrealistic interpretation in Uzbek literature based on the work of Nazar Eshankul. In the writer's stories, the character of the heroes looking for light in the dark is analyzed, and the ways of inspiration of representatives of world literature are expressed. In particular, mental decline and dumbness are the keys to revealing the psyche of the writer's heroes.
Keywords: story; poetics; symbol; allegory; image; plot; character; space; time; modification; composition